Free online trainings on soil health monitoring with satellite based remote sensors - Huq, Rafiq; Lesueur, Didier (2024)
The ASEAN-CGIAR Innovate for Food and Nutrition Security Regional Program (IFNRP) is a collaborative research initiative involving the ASEAN Member States, the ASEAN Secretariat, and CGIAR Centers. This program is funded by the governments of Australia and the United Kingdom. Over the next 10 years, the program aims to expand innovative strategies that will strengthen the resilience of ASEAN’s agri-food systems in response to climate change. This ambitious endeavor seeks to improve livelihoods for food producers and all stakeholders within the value chain. Additionally, it aims to provide consumers with more affordable, nutritious, and healthy food while promoting a healthier natural environment for everyone.